How external and agency characteristics are related to coordination in homecare - findings of the national multicenter, cross-sectional SPOTnat study - Nathalie Möckli; Michael Simon; Kris Denhaerynck; Diana Trutschel; Tania Martins; Carla Meyer-Massetti; Franziska Zúñiga (BMC, 2024)
Abstract Background Homecare client services are often distributed across several interdependent healthcare providers, making proper care coordination essential. However, as studies exploring care coordination in the homecare setting are scarce, serious knowledge gaps exist regarding how various factors influence coordination in this care sector. To fill such gaps, this study's central aim was to explore how external factors (i.e., financial and regulatory mechanisms) and homecare agency characteristics (i.e., work environment, workforce, and client characteristics) are related to care coordination in homecare. Methods This analysis was part of a national multicentre, cross-sectional study in the Swiss homecare setting that included a stratified random sample of 88 Swiss homecare agencies. Data were collected between January and September 2021 through agency and employee questionnaires. Using our newly developed care coordination framework, COORA, we modelled our variables to assess the relevant components of care coordination on the structural, process, and outcome levels. We conducted both descriptive and multilevel regression analyses-with the latter adjusting for dependencies within agencies-to explore which key factors are associated with coordination. Results The final sample size consisted of 1450 employees of 71 homecare agencies. We found that one explicit coordination mechanism ("communication and information exchange" (beta = 0.10, p <.001)) and four implicit coordination mechanisms-"knowledge of the health system" (beta = -0.07, p <.01), "role clarity" (beta = 0.07, p <.001), "mutual respect and trust" (beta = 0.07, p <.001), and "accountability, predictability, common perspective" (beta = 0.19, p <.001)-were significantly positively associated with employee-perceived coordination. We also found that the effects of agency characteristics and external factors were mediated through coordination processes. Conclusion Implicit coordination mechanisms, which enable and enhance team communication, require closer examination. While developing strategies to strengthen implicit mechanisms, the involvement of the entire care team is vital to create structures (i.e., explicit mechanisms) that enable communication and information exchange. Appropriate coordination processes seem to mitigate the association between staffing and coordination. This suggests that they support coordination even when workload and overtime are higher.